Perkembangan Terkini dalam Desain Obat Berbasis Kimia Medisinal - Amin, Saeful; Heryanto, Popih; Athaya, Rahil; Fitri, Nabila Ainul (Penerbit Goodwood, 2025)
Purpose: This study aims to describe recent approaches and innovations in drug design rooted in medicinal chemistry, with particular emphasis on the contributions of computational methods and the exploration of natural compounds in the development of new drug candidates. Methodology/Approach: This literature review synthesizes current research on in silico techniques such as molecular docking, QSAR (Quantitative Structure–Activity Relationship), and ADMET (Absorption, Distribution, Metabolism, Excretion, and Toxicity) prediction. It also examines the integration of natural product screening, synthetic compound optimization, and interdisciplinary approaches involving bioinformatics and pharmacogenomics. Results/Findings: Computational approaches have proven effective in reducing time and costs during the early phases of drug discovery. Natural products provide structurally diverse scaffolds with promising biological activities, particularly in the development of anticancer agents. The combination of medicinal chemistry with interdisciplinary fields enhances mechanistic understanding and supports the rational design of novel therapeutics. Conclusions: The convergence of computational innovation and interdisciplinary research significantly enhances the efficiency, precision, and scope of modern drug design, paving the way for more personalized and targeted therapies. Limitations: This study is based solely on secondary data from published literature and does not include empirical validation through laboratory experiments. Contribution: This review offers a comprehensive overview of emerging trends in medicinal chemistry and serves as a valuable reference for researchers, pharmaceutical scientists, and interdisciplinary teams seeking to advance drug discovery efforts.